NON-ZERO CONSTANT CURVATURE FACTORABLE SURFACES IN PSEUDO-GALILEAN SPACE - Aydin, Muhittin Evren; Kulahci, Mihriban; Ogrenmis, Alper Osman (Korean Mathematical Soc, 2018)
Factorable surfaces, i.e. graphs associated with the product of two functions of one variable, constitute a wide class of surfaces in differential geometry. Such surfaces in the pseudo-Galilean space with zero Gaussian and mean curvature were obtained in [2]. In this study, we provide new results relating to the factorable surfaces with non-zero constant Gaussian and mean curvature.
Keywords: pseudo-Galilean space; factorable surface; Gaussian curvature; mean curvature